The Learning Skills of English as a Foreign Language (EFL) Student-Teachers in Project-based Learning and Case-based Learning - Rosinta Norawati; Yunita Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
As a new curriculum, Merdeka Belajar is expected to provide a learning experience enabling the students to articulate the knowledge and information they obtain to solve real-world problems. It is believed that CBL and PjBL are able to make it happen. Therefore, this study aimed to investigate what learning skills functioned regarding the implementation of case-based learning (CBL) and project-based learning (PjBL); and probe if the two learning models have a statistically significant difference in the learning skills of the student-teachers. A one-group post-test design and non-randomized sampling were used to select the participants. Two sets of questionnaires were administered to 20 EFL student-teachers as participants to obtain their perceptions about the implementation of CBL and PjBL. The findings revealed learning skills that functioned in the use of CBL included cognitive, critical thinking, and communication skills, whereas, in PjBL, they were critical thinking, learning engagement, and cognitive. However, the result of paired sample t-test showed that there was no significant difference statistically between the use of CBL and PjBL on the learning skills of the student-teachers. It is suggested that future researchers investigate the difference between the two learning models in different settings with different designs and large participants.